The development of strategic management: Journal quality and article impact - Franke, Richard H.; Edlund, Timothy W.; Oster, Frederick (Strategic Management Journal, 1990)
Abstract Quality ratings of strategic management journals by experts correlate closely with objective quality measures of current article impact and cumulative journal influence. In part, journal quality seems determined by editors' research stature. Over 12 years, scholarly influence of strategic management periodicals has grown nearly three‐fold, as two new journals directed to conceptual development of management as a whole have risen to prominence. Expansion of strategic management research and growth of its influence may be in response to challenges posed by the continuing crisis of managerial and business performance.